The protective effect of Bifidobacterium bifidum G9-1 against mucus degradation by Akkermansia muciniphila following small intestine injury caused by a proton pump inhibitor and aspirin. (2nd September 2020) - Yoshihara, Tsutomu; Oikawa, Yosuke; Kato, Takayuki; Kessoku, Takaomi; Kobayashi, Takashi; Kato, Shingo; Misawa, Noboru; Ashikari, Keiichi; Fuyuki, Akiko; Ohkubo, Hidenori; Higurashi, Takuma; Tateishi, Yoko; et al.
ABSTRACT: Background: Proton pump inhibitors (PPIs) can alleviate upper gastrointestinal injury but paradoxically exacerbate aspirin (ASA)-induced small intestine injury. In this study, our goal was to simulate this exacerbation by developing an appropriate animal model, which may help in establishing treatments. Methods : Male mice were fed a 60% fructose diet for 9 weeks, then administered 200 mg/kg ASA 3 h before sacrifice. The PPI omeprazole was administered intraperitoneally once daily for 9 weeks. Bifidobacterium bifidum G9-1 was administered orally for the last week. In addition, Akkermansia muciniphila was administered orally for 9 weeks instead of omeprazole. Results : ASA-induced small-intestine injury was observed in high-fructose fed mice. Omeprazole exacerbated ASA-induced intestinal damage, significantly decreased Bifidobacteria levels, and significantly increased A. muciniphila counts in the jejunum. The direct administration of A. muciniphila caused thinning of the jejunum mucus layer, which was also observed in mice that received ASA and omeprazole. On the other hand, the administration of Bifidobacterium bifidum G9-1 inhibited A. muciniphila growth and reduced thinning of the mucus layer. The number of goblet cells in the jejunum was reduced by the administration of ASA and omeprazole, while Bifidobacterium bifidum G9-1 prevented the reduction. Conclusions : These results suggest that omeprazole-induced gut dysbiosis promotes Akkermansia growth and inhibits Bifidobacterium growth, leading to a thinning of the mucus layer through a reduction in goblet cells in the small intestine. Probiotics are, therefore, a promising approach for the treatment of small intestine injury.